Representaciones sociales en torno a la participación en reuniones sociales restringidas durante la pandemia de COVID-19 en adultos jóvenes de Lima Metropolitana - Ruiz Delgado, Juan Carlos (2023)
Attending to restricted social gatherings during the COVID-19 pandemic was a recurrent behavior in young adults in Metropolitan Lima of non-compliance with the preventive measures that contributed to the propagation of COVID-19. However, this behavior occurred in a complex context where different psychological factors and social conditions were in conflict, therefore, creating difficulties to manage this behavior. In that sense, this research aimed to identify and comprehend the social representations related to this behavior in a group of ten young adults from Metropolitan Lima who attended to these social gatherings. This research used a qualitative exploratory and descriptive approach. A purposive sampling method was used to select the participants, and the data was collected through in-depth interviews. Social representations related to this behavior were linked to general perspectives about the pandemic time related to the individual impact of the crisis and to perspectives about the social and political context; risk as a changing element during the pandemic; facilitating elements for the transgression of preventive measures; and attending to restricted social gatherings as an opportunity for reunion and sharing, a way to scape of the difficulties derived from this crisis, and as a decision related mainly to personal responsibility.